The contribution of procurement contract management in attaining value for money in the procurement of works: A case of VETA Kihonda and MVTTC - Sanga, Devotha (Mzumbe University, 2024)
A Dissertation submitted inpartial/fulfillment of the requirements for the Degree of Master of Science in Procurement and Supply Chain Management of Mzumbe University. 2019